Bunatin sebagai Simbol Identitas dan Ekologi Talang Mamak: Analisis Semiotik Peirce - Jefrizal, Jefrizal (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This study analyzes the poetry collection Bunatin by Dheni Kurnia using Charles Sanders Peirce’s semiotic approach, focusing on how signs in the poems construct meaning and represent Bunatin as a symbol of Talang Mamak's cultural identity and ecology. The analysis reveals that Bunatin is not merely a female figure but also a metaphor for Bumi Talang, which has undergone exploitation and social transformation. Using the concepts of sign, object, and interpretant, this study uncovers how the diction in the poems reflects the social struggles and passive resistance of the Talang Mamak community against marginalization and environmental degradation. The use of iconic and indexical elements illustrates the close relationship between humans and nature, reinforcing Bunatin as a collective symbol of ancestral land. The study affirms poetry as a symbolic medium of resistance against environmental exploitation and cultural identity erosion.